Mid-rapidity anti-baryon to baryon ratios in pp collisions at √s = 0.9, 2.76 and 7 TeV measured by ALICE - Abbas, Ehab Gamal; Angelov, Venelin; Busch, Oliver; Fasel, Markus; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; et al. (The European physical journal. C, Particles and fields, 2013)
The ratios of yields of anti-baryons to baryons probes the mechanisms of baryon-number transport. Within the experimental uncertainties and ranges covered by our measurement, these ratios are independent of rapidity, transverse momentum and multiplicity for all measured energies. The results are compared to expectations from event generators, such as PYTHIA and HIJING/B, that are used to model the particle production in pp collisions.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The ALICE collaboration: E. Abbas, V. Angelov, O. Busch, M. Fasel, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, J. Ulrich, M.A. Völkl, Y. Wang, B. Windelband, M. Winn, A. Zimmermann und weitere 958
Gesehen am 28.04.2021